Complete Heart Block in a Case of Rheumatoid Arthritis: Uncommon Presentation of a Common Disease - Singha, Chayan; Zaman, SM Mustafa; Amin, Rasul; Khaled, Fakhrul Islam; Biswas, Eshita; Anwar, AFM Azim; Mumu, Sanjida Anjum (University Heart Journal, 2022)
We report a case of complete heart block (CHB) in a patient with rheumatoid arthritis (RA) because of its atypical presentation, negative Anti CCP and one of the uncommon causes of CHB. It occurs mainly in patients with established erosive nodular RA. It is usually sudden and permanent. It has several mechanisms, but the most common cause is infiltration in or near the AV node or bundle of His. If CHB develop the best option of treatment is the insertion of a permanent pacemaker. The prognosis is usually good provided no other cardiac lesions exist. University Heart Journal 2022; 18(2): 132-134